ANTUSIASME DAN KETERTARIKAN MASYARAKAT DALAM MENGIKUTI AKTIVITAS CAR FREE DAY DI KOTA SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Abstract. The purpose of this research is to determine the community’s enthusiasm andinterest in the city of Semarang on Car Free Day activities. Population and sample inthis research is a community in the city of Semarang, enthusiastic Car Free Dayactivity at Simpanglima. The technique of data collection conducted in this research isthe observation by using questionnaires and data analysis methods used in this study isthe analysis of diskriptif percentage. The results showed that the enthusiasm of thecommunity to follow the Car Free Day activity in the city of Semarang Simpanglimawith percentage is 89,2%. This can be seen in the data tabu-lations that an averagescore of factor of concern is 90.0%, as many as 77.3% chose the factors of relevance, asmuch of the 88,0% vote of confidence factor, as much as 99,7% choose satisfactionfactors. Interest and enthusiasm for the theory of com-munity in following the Car FreeDay activity in the city of Semarang Simpanglima in categories with higher score89,1% percentage is with the major factors that drive was a factor as much as friends96,67%. This can be seen in the data that the intrin-sic 94,0%, as much as 87,25%choose amenities a factor, as many as 75,67% opted for environmental factors.Summary of the results of this research is the community of Semarang had a highpercentage of motivation 89,2% and had a high interest in anyway with the percentage89,1%.